A METHOD FOR IDENTIFICATION OF LATE DEVONIAN-EARLY CARBONIFEROUS CONODONT ELEMENTS IN THIN AND POLISHED SECTIONS - Zhuravlev A.V. (My University, 2002)
A method for conodont identification in thin and polished sections based on morphological and histological features is discussed. The diagnostic key and examples from the Lower Carboniferous of the Subpolar Ural Mountains are given.
Keywords: Carboniferous; Devonian; Paleozoic::Carboniferous; Палеозой::Девонская; Палеозой::Каменноугольная; Paleozoic::Devonian